Development of Banjar Islamic Literature and Its Problems in Islamic Universities in South Kalimantan (Study on the Libraries of Uin Antasari Banjarmasin, IAI Darussalam Martapura, and Stai Rakha Amuntai) - Rahmawati, Laila; Wahdah, Siti (Pascasarjana UIN ANTASARI Banjarmasin, 2021)
Islamic college library as a library under the auspices of an Islamic college, whose teaching and learning activities cannot be separated from Islamic religious values. Islamic literature is the core collection of information. It is important to introduce and preserve local culture through the library by providing local wisdom Islamic literature (Banjar Islamic literature). Especially the development of Banjar Islamic literature in the libraries of UIN Antasari Banjarmasin, IAI Darussalam Martapura, STAI RAKHA Amuntai. Descriptive with the research subjects of the library head and librarian. Data collection by observation, interview and documentation. Using theory from Miles and Huberman and the testing by triangulation. Development of the Banjar Islamic literature collection; The main subjects of the collection are al-qur'an and tafsir, hadith science, kalam science (theology), fiqh, morals and Sufism, Islamic social and culture, Banjar religious organizations philosophy and development, Islamic psychology, sects and beliefs in Islam, history of Islam and biographies of Banjar figures and scholars. The development of Banjar Islamic literature at the South Kalimantan Islamic College Library does have its own policy. However, limited funds and lack of human resources are obstacles to development.